IMPLEMENTASI MODEL PEMBELAJARAN HUMANIZING THE CLASS ROOM UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP NEGERI 1 MAKASSAR - Azis, Putri Athirah; Azis, Budi Utomo Putra (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2024)
This research is a Classroom Action Research (CAR) conducted in two cycles, with several stages in each cycle, namely: planning, action, observation, and reflection. The purpose of this research is to determine whether the implementation of the Humanizing the Classroom learning model can improve the biology learning outcomes of eighth-grade students at SMP Negeri 1 Makassar. The subjects of this research are 28 eighth-grade students at SMP Negeri 1 Makassar in the 2022/2023 academic year. The data collection technique used is the biology learning outcomes test conducted at the end of each cycle. The results of the research show an improvement in the biology learning outcomes of eighth-grade students at SMP Negeri 1 Makassar. This improvement can be seen from the average class score, which was 71% in cycle I and increased to 79.10% in cycle II. Additionally, there was an increase in the percentage of biology learning mastery among eighth-grade students at SMP Negeri 1 Makassar, from 64.28% in cycle I to 89.28% in cycle II.